Spectroscopic studies on Permian plant fossils in the Pedra de Fogo Formation from the Parnaíba Basin, Brazil - D.M. da Conceição (Journal of King Saud University: Science, 2018)
The Pedra de Fogo Formation dated from the early Permian (approximately 280 Mya), belongs to the sedimentary Parnaíba Basin, located in the northeastern region of Brazil. It is recognized by their well preserved plant fossil contents and it is notable for having several fossilized trunks in the life position. This study presents physical and/or chemical properties of the fossilized plants through vibrational spectroscopies, SEM/EDS spectroscopy and X-ray diffraction techniques. Specimens from different localities were selected for the purpose of identifying and characterizing compounds related to the fossilized materials. These different techniques allowed obtaining information from the molecular spectra in organic and inorganic substances, which are present in these stated fossils and in the atomic elements, as well as the crystalline phases. Based on the results duly obtained, we were able to identify the presence of silica and confirm that the dominant process of the fossilized specimens investigated has occurred through quartz silicification with the contribution of persistence from amorphous carbon. Keywords: Vibrational spectroscopies, Fossil plants, Permian Period